Integrating HRM with organizational strategy in Ethiopia: a study of manufacturing companies in Addis Ababa and adjacent zones of Oromia - Tekalign Gidi Kure; Meheret Ayenew Warota (Cogent Business & Management)
The integration of human resource management (HRM) with business strategy is essential for fostering organizational coherence, adaptability, and sustained competitive advantage in complex market environments; conversely, misalignment can result in operational inefficiencies and diminished resilience. The study aimed to assess the integration of HRM into the organizational strategy in Ethiopia, with a specific emphasis on manufacturing companies in Addis Ababa and the adjacent Zone of Oromia. Our study emphasizes the need to move beyond just analyzing statistical relationships and instead focus on the active integration of HRM issues into organizational strategy. We employed a mixed research approach and pragmatism research philosophy, gathering data through a structured questionnaire distributed to 371 respondents and conducting 24 key informant interviews with HR managers from the manufacturing sector. Using Principal Component Analysis (PCA), we have decomposed Strategic HRM into two dimensions: strategic orientation and strategic development. Our findings reveal a strong strategic human resource orientation in Addis Ababa and the adjacent Zone of Oromia’s manufacturing sectors. However, this orientation occurs within an environment of low involvement in strategic development and the absence of a written HR strategy. This decomposition offers organizations a valuable framework for assessing their level of strategic HRM integration. Managers and practitioners need to recognize the significance of strategic orientations and strategic development in strategic HRM.